Description of collective team behaviours and team performance analysis of elite rugby competition via cooperative network analysis. (3rd September 2021) - Novak, Andrew R.; Palmer, Sam; Impellizzeri, Franco M.; Garvey, Cathal; Fransen, Job
ABSTRACT: This study investigated cooperative passing interactions in elite rugby match play. Associations between team network metrics and match outcomes were also investigated. A cross-sectional approach was adopted, using data from four Australian Super Rugby teams, across five seasons. 44, 178 passing actions were included across 321 team-fixture observations. Network metrics were calculated for each positional group within each match, and two statistical models were developed; First: a mixed-effects multinomial regression to identify differences between positional groups; and second: a mixed-effects binomial logistic regression to determine the association between team-level network metrics and match outcomes. Differences were identified between positional groups e.g. Halves had the highest out-degree centrality and betweenness, while Centres had higher eigenvector centrality than all other positions. Within the Forwards pack, the Back Row had greater in-degree, out-degree, and betweenness than the Tight Five. Regarding match outcomes, the model explained only 6.9% of variance, although greater in-degree centralisation (OR = 1.847 [1.241–2.749], p = 0.002) and lower eigenvector centralisation (OR = 0.655 [0.440–0.975]; p = 0.037) were associated with successful outcomes. Cooperative passing networks in rugby union may provide useful information to describe how various positions interact, and some behaviours may contribute towards successful team performance.